The Influence of Financial Literacy and Family Financial Education on Personal Financial Management Behavior with Locus of Control as a Moderating Variable - Maulidina, Alfi Nur; Khusnah, Hidayatul (LP3M Universitas Putra Bangsa, 2025)
This study aims to analyze the role of locus of control in moderating the influence of financial literacy and family financial education on the personal financial management of students at the Faculty of Economics, Business, and Digital Technology, Nahdlatul Ulama University Surabaya. Primary data were collected through an online questionnaire with 100 respondents. The analysis was conducted using WarpPLS 8.0. The results show that financial literacy does not have a significant effect on students’ personal financial management. In contrast, family financial education significantly affects personal financial management. However, locus of control is unable to moderate the relationship between financial literacy or family financial education and personal financial management. Thus, locus of control acts as a homologizer moderation variable in the relationship between financial literacy and personal financial management, and as a predictor moderation variable in the relationship between family financial education and students’ personal financial management.